﻿A new species of Neotoxoscelus Fisher, 1921 (Coleoptera, Buprestidae) from South Korea, with an updated checklist - Donguk Kim; Sang Jae Suh (ZooKeys, 2022)
Neotoxoscelus petilus sp. nov. is described from South Korea. Neotoxoscelus Fisher, 1921 is also a new generic record for South Korea. A key to the Neotoxoscelus species and an updated checklist are provided.